Lycopene and Vascular Health - Mozos, Ioana; Stoian, Dana; Caraba, Alexandru; Malainer, Clemens; Horbańczuk, Jarosław O.; Atanasov, Atanas G. (Frontiers in Pharmacology, 2018)
Lycopene is a lipophilic, unsaturated carotenoid, found in red-colored fruits and vegetables, including tomatoes, watermelon, papaya, red grapefruits, and guava. The present work provides an up to date overview of mechanisms linking lycopene in the human diet and vascular changes, considering epidemiological data, clinical studies, and experimental data. Lycopene may improve vascular function and contributes to the primary and secondary prevention of cardiovascular disorders. The main activity profile of lycopene includes anti- atherosclerotic, antioxidant, antiinflammatory, antihypertensive, antiplatelet, anti-apoptotic and protective endothelial effects, the ability to improve the metabolic profile, and reduce arterial stiffness. In this context, lycopene has been shown in numerous studies to exert a favorable effect in patients with subclinical atherosclerosis, metabolic syndrome, hypertension, peripheral vascular disease, stroke and several other cardiovascular disorders, although the obtained results are sometimes inconsistent, which warrants further studies focusing on its bioactivity.